PERBANDINGAN KINERJA KEUANGAN BANK DEVISA DAN BANK NON DEVISA DI INDONESIA - Sally Ridge Angie Manuputty; Hari Sunarto (Jurnal Riset Akuntansi dan Keuangan, 2013)
This research is aimed at examining whether the foreign exchange banks perform better than non foreign exchange banks. The sample size of both bank categories are drawn almost evenly i.e. twenty fourth foreign exchange banks and twenty fifth non foreign exchange banks as they are listed in the Bank Indonesia for period of 2006 until 2010. The independent sample statistical t-test and U Mann Whitney test are used to examine the hypothesis. Almost all financial ratios as indictors’ bank performance disclose that foreign exchange banks surpass those non foreign exchange banks. The descriptive statistic of financial ratios may reflect the advantage of the former bank category such larger geographic coverage and superiority in management team. However, according inference statistical test came to conclusion that foreign exchange bank performs better significantly in lower operational risk and hence lower cost of fund respectively. The non foreign exchange bank category prove a better in capital adequacy ratio, however the foreign exchange bank category has superior absolute paid up capital. Keywords : financial performance, foreign exchange bank, non foreign exchange bank.